Perception and family social support correlation of pap smear or IVA test participation - irianti, Bayu irianti; Sudrajat, evi chirsty; Lestari, Meti Widiya (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Cervical cancer is a leading cause of mortality among women in developing countries. The low participation of women of reproductive age (WRA) in pap smear or VIA examinations is influenced by negative perceptions of the procedures and a lack of understanding of their processes, despite the frequent availability of social support from families. Objective: To determine the relationship between perception and family social support and the participation of WRA in pap smear or VIA examinations. Methods: This study employed a cross-sectional design with a sample of 208 WRA aged 15–49 years. The independent variables were WRA participation, while the dependent variables included perception and family social support. Data were collected using a validated and reliable questionnaire instrument. Univariate data analysis employed descriptive analysis, while bivariate analysis used biserial correlation tests. Results: The study found that 55% of respondents had negative perceptions, 45% had positive perceptions, 52% reported low family social support, and 48% had full family social support. Regarding participation in cervical cancer screening, 85.6% had never undergone screening, while 14.4% had participated. A significant relationship was observed between perception and participation in screening (p-value = 0.000). Conversely, no significant relationship was found between family social support and participation in screening (p-value = 0.443). Conclusion: A significant relationship between perception and WRA participation in pap smear or VIA examinations. However, no significant relationship was found between family social support and WRA participation in these examinations.